Cigarette Smoking During Pregnancy: Do Complete Abstinence and Low Level Cigarette Smoking Have Similar Impact on Birth Weight?. Issue 5 (11th April 2017) - Berlin, Ivan; Golmard, Jean-Louis; Jacob, Nelly; Tanguy, Marie-Laure; Heishman, Stephen J.
Abstract: Objectives: Despite awareness of negative health outcomes associated with smoking, pregnant smokers might reduce their tobacco consumption thinking that a low smoking rate reduces smoking-related negative birth outcomes. We aimed to assess in a clinical sample whether there is a smoking rate that would not impact on birth weight (BW). Methods: Pregnant smokers ≥18 years, gestational age of 9–20 weeks of amenorrhea, motivated to quit smoking, smoking ≥5 cigarettes/day (cpd) and their newborns (381 singleton, live births) were included in this secondary analysis of a French smoking cessation trial. Results: The mean BW when the mother quit smoking was 3417 g (95 % CI: 3098–3738 g); when smoking >0<5 cpd, 3081g (3003–3159 g); when smoking 5–9 cpd, 3043 g (2930–3157 g); and when smoking ≥10 cpd, 2831 g (2596–3157 g) ( p = .006). The corresponding effect sizes ranged from medium to large (Cohen's d for BW: 0.54, 0.57 and 0.85) compared to BW when the mother quit. In the multivariable analysis, adjusted for all significant confounders, when the mother smoked on average >0<5 cpd, the loss in BW was 228 g; when smoking 5–9 cpd, 251 g; and when smoking ≥10 cpd, 262 g (all p ≤ .02) compared to newborns' BW of mothers who stopped smoking since quit date. Conclusions: Even low cigarette consumption during pregnancy is associated with BW loss. All efforts should be made to help pregnant smokers quit completely during their pregnancy. Implications: As an alternative to quitting smoking, pregnant smokers reduce their smoking rate thinking that this diminishes smoking-related negative health outcomes. No study has established whether low smoking rate (more than 0 but less than 5 cpd) during pregnancy impacts BW compared to abstinence from smoking. Among treatment-seeking pregnant smokers BW of newborns of mothers who smoked even less than 5 cpd was significantly lower than of those whose mothers quit; effect sizes of different consumption levels on BW ranged from moderate (>0<5 cpd) to large (≥10 cpd). Even low smoking rate is associated with reduced BW compared to complete maternal smoking abstinence.